Malevolent alliance of MYBL2hi cancer stem cell and SPP1+ macrophage confers resistance to neoadjuvant immunotherapy in bladder cancer - Lin Ma; Jie Dong; Yingjie Li; Xuebin Zhang; Ziyi Li; Hualin Chen; Yi Xie; Zhaoheng Jin; Yueqiang Peng; Zhigang Ji (Journal for ImmunoTherapy of Cancer, 2025)
Background Neoadjuvant immune checkpoint blockade (nICB) has revolutionized cancer treatment, yet the underlying mechanisms of resistance in bladder cancer remain to be explored.Methods We conducted single-cell RNA sequencing (scRNA-seq) on peripheral blood mononuclear cells, tumor tissues, adjacent normal tissues, and metastatic lymph nodes from 2 nICB-naïve and 10 nICB-treated patients with bladder cancer (5 responders and 5 non-responders). Spatial RNA sequencing was performed on tumor slides from two responders and four non-responders. Findings were validated by multiplex immunohistochemistry, mice orthotopic bladder cancer model, and flow cytometry assays.Results nICB remodeled the tumor microenvironment of bladder cancer from both single-cell and spatial perspectives. scRNA-seq analysis revealed a significant increase in MYBL2hi cancer stem cells (CSCs) among non-responders. Analysis of the myeloid population showed that SPP1+ macrophages associated with angiogenesis were linked to CD8+ T cell exclusion. Further investigation into cell–cell communication revealed a propensity for bidirectional crosstalk between MYBL2hi CSCs and SPP1+ macrophages in non-responders. MYBL2hi CSCs derived CCL15, which bound to CCR1 and induced SPP1 upregulation in macrophages which reciprocally enhanced bladder cancer stemness and resistance to nICB through the SPP1-ITGα9β1 axis. Additionally, we identified an aged CCL3+ neutrophil population that interacted with SPP1+ macrophages through a positive feedback loop, contributing to nICB resistance. Finally, in vivo studies demonstrated that combined MYBL2 knockdown and SPP1 targeting synergistically enhanced ICB efficacy in bladder cancer.Conclusions Our research reveals transcriptomic characteristics associated with distinct therapeutic responses to nICB treatment, offering a foundation for optimizing personalized neoadjuvant strategies in bladder cancer.